Mechanical ventilation in acute brain injury patients with acute respiratory distress syndrome - Humayun, Mariyam; Premraj, Lavienraj; Shah, Vishank; Cho, Sung-Min (Frontiers in Medicine, 2022)
Acute respiratory distress syndrome (ARDS) is commonly seen in patients with acute brain injury (ABI), with prevalence being as high as 35%. These patients often have additional risk factors for ARDS compared to general critical care patients. Lung injury in ABI occurs secondary to catecholamine surge and neuro-inflammatory processes. ARDS patients benefit from lung protective ventilation using low tidal volumes, permissive hypercapnia, high PEEP, and lower PO2 goals. These strategies can often be detrimental in ABI given the risk of brain hypoxia and elevation of intracranial pressure (ICP). While lung protective ventilation is not contraindicated in ABI, special consideration is warranted to make sure it does not interfere with neurological recovery. Permissive hypercapnia with low lung volumes can be utilized in patients without any ICP issues but those with ICP elevations can benefit from continuous ICP monitoring to personalize PCO2 goals. Hypoxia leads to poor outcomes in ABI, hence the ARDSnet protocol of lower PO2 target (55-80 mmHg) might not be the best practice in patients with concomitant ARDS and ABI. High-normal PO2 levels are reasonable in target in severe ABI with ARDS. Studies have shown that PEEP up to 12 mmHg does not cause significant elevations in ICP and is safe to use in ABI though mean arterial pressure, respiratory system compliance, and cerebral perfusion pressure should be closely monitored. Given most trials investigating therapeutics in ARDS have excluded ABI patients, focused research is needed in the field to advance the care of these patients using evidence-based medicine.